2011
DOI: 10.1080/10382046.2011.588501
|View full text |Cite
|
Sign up to set email alerts
|

Urban environmental education: leveraging technology and ecology to engage students in studying the environment

Abstract: In this paper, we describe the outcomes of the first year of an intensive, urban ecology focused, summer program for urban high school youth. Students in our program conduct scientific investigations of their urban ecosystems while exploring potential career options in science and technology fields. In conducting their investigations, the students used geographic information systems (GIS) coupled with computer modeling tools and visualization software to explore the ecological services provided by their urban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 36 publications
1
28
0
1
Order By: Relevance
“…Pruneau, Chouinard, Arsenault, and Breau (1999) developed an educational model to improve people's relationships with their biophysical environments and their communities. Furthermore, Barnett, Vaughn, Strauss, and Cotter (2011) have been striving to engage students in becoming urban ecologists through an evaluation of green spaces' ecological, economic and social benefits for urban residents and emphasis on the built environment's impact on the natural ecosystem. They stated that by engaging students in locally focused, in-depth and targeted environmental science investigations, students could develop the confidence to investigate and solve local problems, increasing their certainty in their ability to study science and perform scientific investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Pruneau, Chouinard, Arsenault, and Breau (1999) developed an educational model to improve people's relationships with their biophysical environments and their communities. Furthermore, Barnett, Vaughn, Strauss, and Cotter (2011) have been striving to engage students in becoming urban ecologists through an evaluation of green spaces' ecological, economic and social benefits for urban residents and emphasis on the built environment's impact on the natural ecosystem. They stated that by engaging students in locally focused, in-depth and targeted environmental science investigations, students could develop the confidence to investigate and solve local problems, increasing their certainty in their ability to study science and perform scientific investigations.…”
Section: Introductionmentioning
confidence: 99%
“…maps, remote sensing imagery, GPS way points, etc.) (Barnett, Vaughn, Strauss, & Cotter, 2011;Campbell, 2008). This type of technology, through the nature and processes of science, can also be expanded into non-science arenas (social welfare, environmental health, etc.…”
Section: Use Of Technologymentioning
confidence: 97%
“…) operating in middle and high schools on a regional or national basis, and organizations like the Technology Student Association, which involves young people in science-and technology-related competitions, claiming memberships of 250,000 young people (Chung, 2006;Technology Student Association, 2018). Though there are scattered studies of individual after-school programs and summer science enrichment efforts (Barker & Ansorge, 2007;Barnett, Vaughn, Strauss, & Cotter, 2011;Chacon & Soto-Johnson, 2003;Fancsali, 2002;Gibson & Chase, 2002;Markowitz, 2004;Weinberg, Pettibone, Thomas, Stephen, & Stein, 2007;Welch, 2010), most of the existing studies focus on short-term outcomes, are based on self-reported impacts, and few incorporate a control or comparison group design (Whitehurst, 2004). Given the growing emphasis on after-school programming in education and in promoting more hands-on learning experiences in science-and technology-related fields, it is becoming increasingly important to better understand the role that after-school science and technology programs can play in moving young people toward STEM-related careers.…”
Section: Introductionmentioning
confidence: 99%